Integrated modelling of conjunctive use of surface and groundwater resources in a small-scale irrigation system in the Volta Basin, Africa - Bharati, Luna; Rodgers, C.; Shumilov, S.; Plotnikova, M.; Vlek, Paul L.G. (2007)
The Volta Basin covers 400 000 km of the West-African Savanna. Agriculture is the dominant ecnomic activity. Given the extremely unreliable rainfall, irrigation development is seen as an obvious strategy to increase agricultural production. Irrigation development is mainly linked to the construction of small and medium sized reservoirs. The potential use of groundwater for irrigation is a very important issue. In this study, we present an evaluation of the conjunctive use of surface and groundwater in a representative small reservoir-irrigation system. The physical processes are modelled with WaSiM-ETH. The physical boundary conditions needed for the optimization model are then passed on to the optimization model written in GAMS, which then simulates the capture and utilization of runoff in small reservoirs. Water can be withdrawn for irrigation, or stored. Irrigation water can also be pumped from the underlying aquifer, and pumping costs are modelled as proportional to the distance to the water table.